For Joshua : an Ojibway father teaches his son - Wagamese, Richard (Milkweed Editions, 2020)
"Richard Wagamese's For Joshua is at once a deeply personal memoir, a search for peace amidst the chaos of human life, and an extended love letter to Wagamese's estranged son"--